2020
DOI: 10.1371/journal.pone.0239383
|View full text |Cite
|
Sign up to set email alerts
|

Work participation and risk factors for health-related job loss among older workers in the Health and Employment after Fifty (HEAF) study: Evidence from a 2-year follow-up period

Abstract: Introduction Rapidly increasing population old age dependency ratios create a growing economic imperative for people to work to older ages. However, rates of older worker employment are only increasing slowly. Amongst a cohort of contemporary older workers, we investigated risk factors for health-related job loss (HRJL) over 2 years of follow-up. Methods HEAF is a population based cohort study of adults in England (aged 50-64 years at baseline) who provided information about socio-demographic characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Accelerated lung function decline, elevated risk of acute mountain sickness 7 were those few among negative health effects of smoking in the working population at high altitude. Consistent with another study of the association of smoking with non-survival at work 23 , we now supplement this notation with a similar effect at the high-altitude mine. Furthermore, in a large 30-year cohort observation of veterans, they demonstrated that smoking-related diseases contributed most in mortality of those who left prematurely 24 .…”
Section: Discussionmentioning
confidence: 54%
“…Accelerated lung function decline, elevated risk of acute mountain sickness 7 were those few among negative health effects of smoking in the working population at high altitude. Consistent with another study of the association of smoking with non-survival at work 23 , we now supplement this notation with a similar effect at the high-altitude mine. Furthermore, in a large 30-year cohort observation of veterans, they demonstrated that smoking-related diseases contributed most in mortality of those who left prematurely 24 .…”
Section: Discussionmentioning
confidence: 54%
“…However, the GAR cohort included more men than women. Sampling was based on age at THA and a minimum duration of follow-up postoperatively rather than work status but these differences are potentially important because men and women tend to undertake different types of occupations 38. Specifically, men are more likely to undertake the more physically demanding occupations.…”
Section: Discussionmentioning
confidence: 99%
“…The principal objective of our analysis was to estimate the effect of slow walking speed (the ‘exposure’) on risk of HRJL (the ‘outcome’) with appropriate adjustment for the role of potential confounders. As previously, 26 men and women were analysed separately; an analysis strategy decided a priori because work and its social context typically differ between men and women, 27 28 and previous research has called for investigation of gender differences in risk factors for HRJL. 29 Analyses were conducted using the Stata statistical software package (release 15).…”
Section: Methodsmentioning
confidence: 99%